Attention modulates initial stages of visual word processing. - Ruz, M; Nobre, A (2008)
Selective attention has the potential to enhance the initial processing of objects, their spatial locations, or their constituent features. The present study shows that this capacity to modulate initial stages of processing also applies to linguistic attributes. A cueing paradigm focused attention at different levels of word representations on a trial-by-trial basis to study the time course of attentional modulation on visual word processing by means of a high-density electrophysiology recording system. Attention to different linguistic attributes modulated components related to semantic, phonological, and orthographic stages of word processing. Crucially, the N200, associated with initial stages of orthographic decoding, was enhanced by attention to the letter pattern of words. These results suggest that top-down attention has the capacity to enhance initial perceptual stages of visual word processing and support the flexibility of attention in modulating different levels of information processing depending on task goals.